Assessment of disassembly difficulty level of lithium battery pack by integrating Ease of Disassembly Metric (eDiM) and difficulty rating approach - Muqimuddin, Muqimuddin; Utomo, Dutho Suh; Farid, Nik Mohd; Armia, Iin; Dimyati, Aufar Fikri; Gunawan, Gad; Zamzani, Muhammad Imron (OPSI, 2025)
The demand for batteries is expected to rise in line with the growing need for electric vehicles. As the number of electric vehicles increases, more battery waste will be generated, considering the average battery lifespan is only 10 to 15 years. If batteries are not recycled, this will lead to a significant accumulation of waste. Therefore, it is important to evaluate the ease of battery disassembly. This assessment can help manufacturers design batteries that are easier to disassemble. This study aims to determine the disassembly ease score and provide improvement recommendations using the Ease of Disassembly approach through eDiM and Difficulty Rating. The disassembly process is analyzed using the Ease of Disassembly Metric (eDiM) to evaluate difficulty levels based on standard disassembly operation time, and Difficulty Rating based on the indicators of Accessibility, Positioning, and Force. Based on the analysis results, the most difficult disassembly operations involve removing screws from the top cover, bottom cover, controller circuit, and BMS circuit, as well as detaching the nickel strip. The research findings indicate the presence of disassembly stages with low time values but high preference-based difficulty levels.